Study of a continuous process of glycerolysis of rapeseed oil with the solid base catalysts - Brei, Volodymyr; Starukh, Galyna; Levytska, Svitlana; Shistka, Dmytro (Publishing House of Lviv Polytechnic National University, 2012)
Glycerolysis of rapeseed oil over several solid bases using fixed bed flow reactor has been studied. It was found that Mg-Al hydrotalcite and Al2O3 supported CaO–ZnO demonstrate high activity in this reaction. The yield of monoglycerides reaches 70 % with 96 % oil conversion at 513 K. It was shown that pores size of a catalyst is an important factor of intensification of the glycerolysis process. It was found that turpentine additive decreases the reaction temperature due to higher solubility of glycerol in oil. Досліджено процес гліцеролізу ріпакової олії на твердих основних каталізаторах в проточному реакторі зі стаціонарним шаром каталізатора. Знайдено, що Mg-Al-гідроталькіт і CaO-ZnO/Al2O3 проявляють високу активність в цій реакції. Вихід моногліцеридів досягає 70 % при 96 % конверсії олії за 513 K. Показано, що розмір пор каталізатора є важливим фактором в процесі гліцеролізу. Знайдено, що додавання скипидару дозволяє знизити температуру реакції завдяки збільшенню розчинності гліцерину в олії.
Вивчення нестаціонарного процесу гліцеролізу ріпакової олії на основних каталізаторах
Keywords: solid base catalysts; hydrotalcite; rapeseed oil glycerolysis; monoglycerides; тверді основні каталізатори; гідроталькіт; гліцероліз ріпакової олії; моногліцериди